Boolean algebras with a distinguished automorphism - Abad, Manuel (2003)
In this paper we investigate a subvariety BA of tense algebras, which we call Boolean algebras with a distinguished automorphism. This variety provides a unifying framework for the algebras studied by Monteiro in [4] and by Moisil in [5,6]. Among others we prove that BA is generated by its finite members and we characterize the locally finite subvarieties of BA